Dynamic Modeling of Service Quality Improvement through Feedback-Based Governance - Wildan Alrasyid; Galih Prakoso Rizky A; Budi Arif Dermawan; Rasenda Rasenda (International Journal of Enterprise Modelling, 2026)
This study aims to develop a dynamic system model designed to improve service quality and reduce the gap between the expected and actual levels of community satisfaction. The study is motivated by the importance of understanding the interaction between key variables such as human resources (HR), information and communication technology (ICT), and evaluation mechanisms within a feedback-based service system. The system dynamics method is employed to construct causal loop and stock–flow models to simulate their impacts over a 12-month period. The simulation results show that strengthening HR, ICT, and evaluation aspects leads to a significant improvement in service quality, which directly increases community satisfaction. In addition, the gap between actual and targeted satisfaction shows a decreasing trend over time. Community feedback emerges as a crucial factor that accelerates performance improvement through reinforcing loops. Graphical and tabular representations support the positive dynamics of the main variables and demonstrate the system’s flexibility in responding to internal changes. This study demonstrates that dynamic system modeling is an effective approach to managing complex service systems. By illustrating nonlinear interactions among variables and considering time delays, decision-makers can simulate policy impacts before implementation. The study concludes that feedback-based models can serve as useful tools for simultaneously improving public services and reducing performance gaps.